Knowledge, attitude, and experience of menopause of female prisoners - Firdos; Najam-ul-sabha; Rifat Latif; Asifa Shahzadi (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: All women experience menopause in their late forties, sufficient knowledge and a positive attitude about menopause is essential for women to overcome the changes associated with menopause. Female prisoners have significant unmet needs related to transitional menopause experience because a majority of them are illiterate and from an underprivileged class and limited access to health services. Our objective is to explore the menopause experiences of women incarcerated in jail.METHODOLOGY: A semi-structured questionnaire was used, 48 women were interviewed using face-to-face interview technique. Participants were selected by convenience sampling. The study was conducted in Kot Lakh Pat jail Lahore among female prisoners, age ranging from 40 to 60 years.RESULTS: Mean age of women was 45.4 +4.6 years, about 44(91.6%) were aware of menopause, while only 4(8.3%) were aware of its health effects. 44(91.6%) of female prisoners viewed it as a natural process, and 4(8.3%) viewed it as a disease. 41(85.4%) of women are happy with the transition to menopause, while 7(14.5%) are anxious and want to menstruate again. There were statistically significant differences in the Somatic symptoms and psychological symptoms (p<0.05).CONCLUSION: The majority of female prisoners were concerned about symptoms even though they did not go for consultation due to a lack of information and health services in prison. To increase public health awareness and reduce the magnitude of menopause-related symptoms, there is a need to develop health care services in the context of treatment and prevention for women prisoners in their present locality.